2000
DOI: 10.1071/pp00025
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium cells as microprojectile coating: a novel approach to enhance stable transformation rates in strawberry

Abstract: The effect of combining Agrobacterium tumefaciens infection and biolistic bombardment on the transformation of strawberry (Fragaria × ananassa Duch.) cv. Chandler, was evaluated. Bombarding leaf explants with uncoated gold particles followed by Agrobacterium infection did not improve transformation, and yielded similar percentages of shoot regeneration in the presence of kanamycin in bombarded and non-bombarded explants (7.2%). In a novel approximation, gold particles were coated with Agrobacterium cells and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Effective selection, using suitable selectable marker genes, can lead to a substantial reduction in the number of untransformed regenerants [42]. Most binary vectors used for transformation of strawberry carry the nptII gene conferring kanamycin resistance [10,33,44,45,46]. Based on the literature the possible doses of kanamycin that have been applied for selection of putative transformants from leaf explant of strawberry ranged from 25 mg/L [47,48] to 50 mg/L [33,49].…”
Section: Resultsmentioning
confidence: 99%
“…Effective selection, using suitable selectable marker genes, can lead to a substantial reduction in the number of untransformed regenerants [42]. Most binary vectors used for transformation of strawberry carry the nptII gene conferring kanamycin resistance [10,33,44,45,46]. Based on the literature the possible doses of kanamycin that have been applied for selection of putative transformants from leaf explant of strawberry ranged from 25 mg/L [47,48] to 50 mg/L [33,49].…”
Section: Resultsmentioning
confidence: 99%
“…and wild strawberry ( F. vesca ) have already been reported. Although they are considered to be relatively amenable to transformation using Agrobacterium ( ), transformation frequencies are greatly influenced by the cultivar and the procedure used ( , ). The technique is being used successfully to genetically engineer virus resistance ().…”
Section: Introductionmentioning
confidence: 99%
“…by combining Agrobacterium infection and particle bombardment. [ 56 ] They found that gold particles coated with Agrobacterium could achieve increased expression of β‐glucuronidase (GUS) within 15 days after particle bombardment, while uncoated gold particles did not improve GUS expression. Therefore, the combined use of Agrobacterium and particle bombardment can achieve higher transformation efficiency in certain plants.…”
Section: Traditional Plant Transformation Methodsmentioning
confidence: 99%
“…by combining Agrobacterium infection and particle bombardment. [56] They found that gold particles coated with Agrobacterium could achieve increased expression of β-glucuronidase (GUS) within 15 days after particle Adv. Mater.…”
Section: Biolistic Particle Deliverymentioning
confidence: 99%